MUC5AC enhances tumor heterogeneity in lung adenocarcinoma with mucin production and is associated with poor prognosis. (21st February 2020) - Dong, Yujie; Zhou, Lijuan; Zhao, Dan; Li, Kun; Liu, Zichen; Che, Nanying; Liu, Honggang
Abstract: Objective: The clinicopathological significance of Mucin5AC ( MUC5AC ) in lung adenocarcinoma with mucin production is still unclear. This study aimed to explore MUC5AC expression in lung adenocarcinoma with mucin production and its correlation with histological subtypes, common driver mutations and its impact on prognosis. Methods: MUC5AC and thyroid transcription factor 1 immunohistochemistry was performed on surgical samples from 90 patients with lung adenocarcinoma with mucin production. Common driver mutations including EGFR and KRAS mutations and ALK rearrangement were detected by established methods. Results: MUC5AC was significantly associated with lymphovascular invasion ( P = 0.023) and tumors with intra-cytoplasmic mucin ( P < 0.001). Moreover, MUC5AC was more significant in invasive mucinous adenocarcinoma ( P < 0.001), as well as in tumors with KRAS mutations ( P = 0.005) and a lack of thyroid transcription factor 1 expression ( P < 0.001). Conversely, MUC5AC was less significantly detected in acinar predominant adenocarcinoma ( P = 0.036) and tumors with EGFR mutations ( P = 0.001). Notably, MUC5AC in non-pure mucinous subtype of lung adenocarcinoma with mucin production showed more aggressive behavior, distinct expression pattern and a lack of significant correlation with thyroid transcription factor 1 ( P = 0.113) when compared with pure mucinous subtype. MUC5AC -positive tumors were significantly associated with a worse prognosis compared to MUC5AC -negative tumors ( P < 0.001). A multivariate survival analysis showed that MUC5AC was an independent prognosis factor for poor prognosis ( P = 0.006). Conclusions: The clinicopathological features of non-pure mucinous subtype of lung adenocarcinoma with mucin production were distinct and should be distinguished from pure mucinous subtype. MUC5AC was associated with poor prognosis and could be a potential therapeutic target for this distinct type of lung adenocarcinoma that has few effective treatments. Abstract : The present study explored MUC5AC in lung adenocarcinoma with mucin production. MUC5AC and its impact of prognosis in different mucinous subtypes are distinct. These findings strongly demonstrate the heterogeneity of lung adenocarcinoma with mucin production.